The influence of educational and professional activity on the socialization of students - Sokolovskaya, Irina E.; Polevoy, Sergey A.; Mikhaylovsky, Mikhail N.; Zotova, Larisa E.; Bazhdanova, Yuliya V.; Egorova, Eleonora V. (Opción, 2020)
The study aims to investigate the influence of educational and professional activity on the socialization of students at a higher education institution via comparative qualitative research methods. As a result, the development level of the individual human capital index is higher in the control group. The conclusions have been drawn that the modernization of the Russian state, socio-economic political transformations, a difficult situation on the labor market have revealed the need for specialists with an active lifestyle, competitive, mobile, able to realize the professional potential, leading a healthy lifestyle.